Membangun Budaya Anti-Korupsi melalui Pembelajaran PPKn di Sekolah Dasar - Erwin Eka Saputra (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Anti-corruption education is one of the important aspects in character building of the young generation, especially at the elementary school level. Pancasila and Citizenship Education (PPKn) learning has a strategic role in instilling the values ​​of honesty, responsibility, and integrity from an early age. This literature study aims to analyze the role of PPKn learning in building an anti-corruption culture in elementary schools. The method used is a literature review of various previous studies that discuss strategies, effectiveness, and challenges in implementing anti-corruption education in the PPKn curriculum. The results of the study show that a value-based learning approach, contextual methods, and active involvement of students in discussions and simulations of real cases can increase awareness and attitudes of anti-corruption in children. In addition, the role of teachers as facilitators and role models in implementing these values ​​also greatly determines the success of this program. The conclusion of this study confirms that the integration of anti-corruption education in PPKn needs to be strengthened with an innovative approach and support from various parties in order to form the character of students with integrity from an early age.